2011
DOI: 10.5771/2192-4007-2011-2-265
|View full text |Cite
|
Sign up to set email alerts
|

Finding Europe: Mapping and explaining antecedents of ‘Europeanness’ in news about the 2009 European Parliamentary Elections

Abstract: Previous research has characterized European news coverage as mainly domestic in focus, hampering the emergence of a European public sphere. This study analyses the European nature of the news coverage of the 2009 European Parliamentary elections. We not only describe the level of Europeanness in news coverage but also propose a comprehensive model to explain differences across countries. We employ a cross-national media content analysis (N=52.009) conducted in all 27 EU member states. Findings show that espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Europeanness in the news can be assessed by different dimensions pertaining to Europeanisation as a vertical or horizontal process, with vertical Europeanisation looking at attention from national media to EU actors and institutions and horizontal Europeanisation at actors and issues from other Member States (Koopmans & Erbe ). Indicators include the prominence of EU actors in news coverage (vertical), the prominence of EU issues (vertical), the location at which the action depicted in a story is taking place (mostly horizontal), or the location of the entity that is depicted as being affected (mostly horizontal) (Schuck & de Vreese ; see also Trenz ).…”
Section: Europe In the News: Dimensions Of The Coveragementioning
confidence: 99%
See 2 more Smart Citations
“…Europeanness in the news can be assessed by different dimensions pertaining to Europeanisation as a vertical or horizontal process, with vertical Europeanisation looking at attention from national media to EU actors and institutions and horizontal Europeanisation at actors and issues from other Member States (Koopmans & Erbe ). Indicators include the prominence of EU actors in news coverage (vertical), the prominence of EU issues (vertical), the location at which the action depicted in a story is taking place (mostly horizontal), or the location of the entity that is depicted as being affected (mostly horizontal) (Schuck & de Vreese ; see also Trenz ).…”
Section: Europe In the News: Dimensions Of The Coveragementioning
confidence: 99%
“…Previous research has found that public broadcasters – endowed with an obligation to inform about politics and public affairs – are more likely to cover European affairs and to be more European in focus than their commercial counterparts (Peter & de Vreese ; Schuck & de Vreese, ). This has also been the case for ‘quality’ broadsheets vis‐à‐vis tabloid‐style newspapers (Trenz ).…”
Section: Understanding News Variation: Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal consistency of the scale was measured using Cronbach's alpha (alpha = .761). The scale was adapted from classical scales used to measure political efficacy (Gerber et al 2011;Gallego and Olberski 2011;Schuck and de Vreese 2011). For the efficacy scale, '1' represents people's trust that they can change or have an influence on or at least matter to the government, while '7' stands for a general sense of powerlessness people associate with politicians and politics in general.…”
Section: Methodsmentioning
confidence: 99%
“…The same agenda-setting mechanisms pursued by political parties and found in a national context could pertain, or even be more pronounced, in a European context for at least two reasons. First, since the EU on its own has little news value (Statham 2008), it needs to be promoted by political actors, such as parties or candidates, to be visible (Adam 2007;De Vreese 2003;Jalali and Silva 2011;Machill et al 2006;Schuck and De Vreese 2011). Second, the introduction of the "Spitzenkandidaten" for the presidency of the European Commission (Van der Brug et al 2016) personalized the 2014 EP election and led to a party-driven rise in media attention (Schulze 2016).…”
mentioning
confidence: 99%